Susceptor-assisted fast microwave sintering of TiN reinforced SiAlON composites in a single mode cavity. Issue 1 (1st January 2021) - Canarslan, Özgür Sevgi; Koroglu, Levent; Ayas, Erhan; Canarslan, Necip Suat; Kara, Alpagut; Veronesi, Paolo
Abstract: In the present study, 17 wt % TiN reinforced α-β SiAlON composites were sintered at low temperature by susceptor-assisted microwave heating. The effect of TiN addition on dielectrical properties of starting powders, as well as the influence of sintering temperature on phase evolution, microstructure development and mechanical properties of α/β-SiAlON-TiN composites were investigated. The obtained results showed that TiN addition increased the microwave absorbing properties which is reflected in the peak sintering temperature. Thus, the α:β ratio decreased and mechanical properties were improved, especially the fracture toughness of the composites. Furthermore, an estimate of energy consumption during microwave assisted sintering at the laboratory scale is presented. As a result, the highest values for relative density (97.1%), Vickers hardness (13.35 ± 0.47 GPa), and fracture toughness (7.52 ± 0.54 MPa m 1/2 ) were obtained by microwave sintering for 30 min at 1300 °C. Graphical abstract: Image 1